2021
DOI: 10.3389/fcvm.2021.723542
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Echocardiography Assessment of Coronary Microvascular Function in Patients With Angina and No Obstructive Coronary Artery Disease

Abstract: Echocardiographic evaluation is an essential part of the diagnostic work-up in patients with known or suspected cardiovascular disease. Transthoracic Doppler echocardiography (TTDE) enables straightforward and reliable visualization of flow in the left anterior descending artery. In the absence of obstructive coronary artery disease, low TTDE-derived coronary flow velocity reserve (CFVR) is considered a marker of coronary microvascular dysfunction (CMD). TTDE CFVR is free from ionizing radiation and widely ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 128 publications
0
9
0
2
Order By: Relevance
“…2.4 Image analysis standards <1>. The AS-MCE data saved above were analyzed by software, and a region of interest (5 mm×5 mm) was set in the center of each segment according to the left ventricular 16segment analysis method [14] , from which a time-intensity curve was generated, and the start was set to the rst frame after Flash followed by reperfusion. Peak signal intensity (A-value), upward slope of the curve (β value), and A×β value (re ecting myocardial blood volume) were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…2.4 Image analysis standards <1>. The AS-MCE data saved above were analyzed by software, and a region of interest (5 mm×5 mm) was set in the center of each segment according to the left ventricular 16segment analysis method [14] , from which a time-intensity curve was generated, and the start was set to the rst frame after Flash followed by reperfusion. Peak signal intensity (A-value), upward slope of the curve (β value), and A×β value (re ecting myocardial blood volume) were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of GLS in evaluating LV function among patients with ANOCA and CMD is controversial. More recently, Schroder J and colleagues suggested that GLS is diminished among patients with ANOCA, and this is linked intricately to CFVR ( 5 ). In contrast to their study, GLS in our study was similar between the control group and CMD group.…”
Section: Discussionmentioning
confidence: 99%
“…However, targeting the distal of left anterior descending artery (LAD) by transthoracic doppler echocardiography makes it possible to infer coronary microvascular function indirectly. In patients not suffering from epicardial disease, a decrease of coronary flow velocity reserve (CFVR) during drug-induced stress can reflect the function of coronary microvascular ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary flow reserve testing was performed using a previously published and validated protocol ( 15 ). The mid-distal segment of the left anterior descending (LAD) branch was identified in the interventricular sulcus under a modified left ventricular double-chamber view, and the flow spectrum was recorded by color Doppler echocardiography to detect the mid-distal coronary artery flow in the left anterior descending branch.…”
Section: Methodsmentioning
confidence: 99%